2023
DOI: 10.1111/nph.19264
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype‐resolved genome assembly provides insights into the evolution of S‐locus supergene in distylous Nymphoides indica

Jingshan Yang,
Haoran Xue,
Zhizhong Li
et al.

Abstract: Summary Distyly has evolved independently in numerous animal‐pollinated angiosperm lineages. Understanding of its molecular basis has been restricted to a few species, primarily Primula. Here, we investigate the genetic architecture of the single diallelic locus (S‐locus) supergene, a linkage group of functionally associated genes, and explore how it may have evolved in distylous Nymphoides indica, a lineage of flowering plants not previously investigated. We assembled haplotype‐resolved genomes, used read‐cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 117 publications
1
7
0
Order By: Relevance
“…We then asked whether the S -locus was hemizygous also in P. edelbergii , as found in all other heterostylous species studied to date (Fawcett et al, 2023; Gutiérrez-Valencia et al, 2022; Li et al, 2016; Shore et al, 2019; Yang et al, 2023; Zhao et al, 2023), by checking whether the S -locus region was characterized by halved sequencing depth, an approach commonly used to detect hemizygous supergenes (Gutiérrez-Valencia et al, 2021). The S -locus had approximately the same sequencing depth as the rest of chromosome 2 (mean S -locus depth: 154.6x; mean chromosome 2 depth: 156.1x; Figure 4d ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then asked whether the S -locus was hemizygous also in P. edelbergii , as found in all other heterostylous species studied to date (Fawcett et al, 2023; Gutiérrez-Valencia et al, 2022; Li et al, 2016; Shore et al, 2019; Yang et al, 2023; Zhao et al, 2023), by checking whether the S -locus region was characterized by halved sequencing depth, an approach commonly used to detect hemizygous supergenes (Gutiérrez-Valencia et al, 2021). The S -locus had approximately the same sequencing depth as the rest of chromosome 2 (mean S -locus depth: 154.6x; mean chromosome 2 depth: 156.1x; Figure 4d ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, research on the S-locus has expanded from Primula to other genera that independently evolved heterostyly, including Turnera (Henning et al, 2022;Matzke et al, 2020Matzke et al, , 2021Shore et al, 2019), Fagopyrum (Fawcett et al, 2023;Yasui et al, 2012Yasui et al, , 2016, Linum (Gutiérrez-Valencia et al, 2022), Gelsemium (Zhao et al, 2023), and Nymphoides (Yang et al, 2023). Surprisingly, in all these cases the S-locus was found to be hemizygous in thrums and absent from pins, pointing to a remarkable consistency in the genomic architecture of the S-locus across heterostylous taxa.…”
Section: Introductionmentioning
confidence: 99%
“…While earlier theory posited that rare recombination events between the recessive and dominant alleles at the S -locus were the cause for distyly breakdown (Dowrick 1956, Charlesworth and Charlesworth 1979a), recent findings have indicated that distyly S- loci harbor presence-absence variation and that thrums are predominantly hemizygous at the S -locus rather than heterozygous (Li et al 2016, Shore et al 2019, Gutiérrez-Valencia et al 2022a, Fawcett et al 2023, Yang et al 2023, Zhao et al 2023). These findings make previous models of breakdown less likely and indicate that mutations either at the S- locus or at unlinked modifier loci are more plausible causes for the evolutionary shift from distyly to homostyly.…”
Section: Discussionmentioning
confidence: 99%
“…It is only recently that distyly supergenes have begun to be sequenced and characterized in detail (reviewed in Gutiérrez-Valencia et al 2021). So far, characterization of independently evolved distyly supergenes in six systems ( Primula : Li et al 2016, Turnera : Shore et al 2019; Linum : Gutiérrez-Valencia et al 2022a, Fagopyrum : Yasui et al 2012, Fawcett et al 2023, Gelsemium : Zhao et al 2023; Nymphoides indica : Yang et al 2023) suggest a remarkable degree of convergence in the genetic architecture of distyly supergenes. Common features of independently evolved distyly supergenes include a genetic architecture featuring length differences between the dominant and recessive supergene haplotypes, resulting in hemizygosity in thrum individuals and thrum-specific expression of S- linked genes (Gutiérrez-Valencia et al 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…It is only recently that distyly supergenes have begun to be sequenced and characterized in detail (reviewed in Gutiérrez-Valencia et al 2021 ). So far, characterization of independently evolved distyly supergenes in six systems ( Fagopyrum : Yasui et al 2012 ; Fawcett et al 2023 ; Primula : Li et al 2016 ; Turnera : Shore et al 2019 ; Linum : Gutiérrez-Valencia et al 2022a ; Nymphoides indica : Yang et al 2023 ; Gelsemium : Zhao et al 2023 ) suggest a remarkable degree of convergence in the genetic architecture of distyly supergenes. Common features of independently evolved distyly supergenes include a genetic architecture featuring length differences between the dominant and recessive supergene haplotypes, resulting in hemizygosity in thrum individuals and thrum-specific expression of S- linked genes ( Gutiérrez-Valencia et al 2022a ).…”
Section: Introductionmentioning
confidence: 99%